Investigation of the influence of the properties of the work and tool materials on performance level of Electrical Discharge Machining (EDM) process - A.K.M., N. Amin; A. K., Sardar (n.p., 1997)
Influence of the properties of work and tool materials on material removal rate (MRR), wear ratio (WR), thickness of the recast layer, surface roughness and accuracy of machining in EDM process was investigated. Copper, brass, stainless steel, mild steel and grey cast iron were used in various combinations as work and tool materials. From the experimental results it was observed that the curves of MRR versus machining time show convex behavior, specially after long duration of machining. It was also observed that the MRR and WR are inversely proportional to the melting points of the work and tool materials respectively. Though electrical conductivity of the tool material was found to have influence on tool wear ratio but brass tool was found to have minimum wear ratio although its electrical conductivity was next to copper. From the bar chart of the recast layer thickness it was observed that for all combinations of work and tool material the thickest recast layer was formed in the case of copper electrode. Photo micrographs of the machined surface reveal that micro cavities formed in the cases of lower melting point electrode materials like copper and brass having higher electrical conductivity are comparatively smaller in size (2-3 μm) as compared to the sizes of the micro cavities (8-20 μm) formed in the cases of high melting point electrodes also having lower electrical conductivity. Consequently the machined surface roughness in the latter cases is higher. It was also observed that the tendency of debris concentration is at the middle of the tool job interface resulting in high bottom surface inaccuracy, specially when high melting point work material are machined by low melting point electrodes like brass. On the basis of material removal rate, wear ratio and job surface finish brass electrodes were found to be most suitable.